AI Illustrative Works: Originality and Copyright in Indonesian and Swedish Law - Rizqi Marhamah, Naeli; Ruhtiani, Maya; Puspa Dewi, Monica (LPPM Universitas Harapan Bangsa, 2025)
The emergence of AI-generated illustrations challenges copyright frameworks globally. This normative study compares Indonesia's static Copyright Law with Sweden's progressive EU-aligned system. While both jurisdictions deny copyright to purely AI-created works due to unmet originality requirements, Sweden's sophisticated approach through neighboring rights and AI Sweden's R&D initiatives demonstrates greater adaptability. Indonesia's rigid human authorship mandate under Article 1(2) UUHC 28/2014 risks technological irrelevance. The analysis recommends Indonesia establish specialized AI governance mechanisms and adopt tiered protection for human-AI collaborations, emulating Sweden's balanced approach under the EU AI Act. Strategic alignment with WIPO standards could bridge the growing regulatory gap while preserving creator rights. The findings highlight the urgent need for developing nations to modernize intellectual property systems in response to disruptive technologies. Sweden's dual strategy of legislative harmonization and research investment offers a replicable model for jurisdictions facing similar AI challenges. This comparative analysis contributes to global discourse on copyright adaptation in the age of generative AI.